Educational Administration Enhancing Graduate’s Competency Employability in Business Vocational Colleges under Chongqing Province - Xiao fei, Zhong; Jirarotephinyo, Nitwadee; Viphoouparakhot, Vorachai (APHEIT International Journal of Interdisciplinary Social Sciences and Technology, 2023)
The objectives of this research were to propose a model for educational administration enhancing graduate’s competency employability in Business Vocational Colleges under Chongqing Province, the People’s Republic of China. This study adopted a mixed methods research design. This topic combined an in-depth interview and questionnaire survey for comprehensive data analysis. The key respondents were 17 managers obtained by the purposive sampling method. Data were collected by in-depth interview with semi-structure questions and the collected data were analyzed by content analysis. The results of the analysis showed that the tree of the graduates’ employability model affecting graduates’ employability for the school education management included: 1) school-enterprise cooperation, employability cultivation, strengthening connotation construction, semi-structure and teaching management, highlighting employability cultivation; 2) ordering professional settings; 3) integrate teaching design of post and class certificate, the teaching mode implementing the "academic certificate + several vocational skills level system; 4) guarantee the investment of teaching funds, improve the teaching level of teachers and practical teaching experience; 5) improve career planning; 6) career tracking and guidance function.